Flood and Megaflood Processes and Deposits 2002
DOI: 10.1002/9781444304299.ch14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land‐Use and Precipitation Changes on Floodplain Sedimentation in the Nineteenth and Twentieth Centuries (Geul River, The Netherlands)

Abstract: flowing through France, Belgium and The Netherlands; Fig. 1a) flooded severely, causing extensive damage and forcing massive evacuations. These events sparked an interest in land-use and climate change as possible causes of the recent, apparent increase in flood frequency. To separate the effects of land-use change and precipitation variability on the peak discharges of the Meuse, one would ideally need single cause-effect relationships for discrete time periods and a long discharge time-series. For a river ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 13 publications
1
27
0
2
Order By: Relevance
“…5), causing severe contamination of fluvial deposits. Previous studies (Stam, 1999(Stam, , 2002 have shown that peaks in heavy metal concentrations in fluvial deposits can be linked with peaks in 19 th century mining activities. Where previous studies focused on profiles at cutbanks, we sampled within the alluvial plain to get a better spatial distribution of sampling sites over the floodplain.…”
Section: Dating Of Floodplain Depositsmentioning
confidence: 99%
See 1 more Smart Citation
“…5), causing severe contamination of fluvial deposits. Previous studies (Stam, 1999(Stam, , 2002 have shown that peaks in heavy metal concentrations in fluvial deposits can be linked with peaks in 19 th century mining activities. Where previous studies focused on profiles at cutbanks, we sampled within the alluvial plain to get a better spatial distribution of sampling sites over the floodplain.…”
Section: Dating Of Floodplain Depositsmentioning
confidence: 99%
“…Additional age control is derived if the temporal variations in tracer introductions are known, as these can be linked to tracer concentrations in the floodplain deposits (e.g. Stam, 1999Stam, , 2002.…”
Section: Dating Of Floodplain Depositsmentioning
confidence: 99%
“…It is expected that less significant and higher frequency flood flows including those in which channels run from bank to bank, impose their own record on the channel (Stam, 2002). The cycles of recurrent flooding in this area of the basin generated a thick sequence with typical deposits produced by ephemeral streams in sheet flood events and the absence of clay-size components in the flood environments.…”
Section: Stratigraphic Architecture Of the Terminal Fan Systemmentioning
confidence: 99%
“…In this perspective, it is our objective to provide in this paper a framework for a better understanding of frequency and magnitude of flooding, and thus help in river management. As a case study, we deal with the lower Maas River valley and one of its main tributaries in The Netherlands, the Geul River (Stam, 2002;De Moor, 2006; for location see Fig. 1).…”
Section: Concepts Of Dynamic Equilibrium Of Interest For River Managementioning
confidence: 99%